2020
DOI: 10.1159/000505973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Systemic Inflammatory Response and Nutritional Biomarkers as Predictive Factors in Patients with Recurrent Gastric Cancer

Abstract: Background: The present study sought to evaluate host-related factors as predictors in patients receiving chemotherapy for recurrent advanced gastric cancer. Methods: Sixtythree patients were enrolled in the study and received chemotherapy for recurrent gastric cancer at the Kochi Medical School from 2008 to 2015. Clinicopathological information and systemic inflammatory response data were obtained retrospectively to investigate associations between baseline cancer-related prognostic variables and survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Although the mechanism by which systemic inflammatory response markers influence cancer survival in these patients remain unclear, it is possible that pretreatment neutrophil and lymphocyte numbers reflect the level of inflammation within the tumor (24). Evidence is accumulating that cancer progression is influenced by the systemic inflammatory response (10,24,25). Furthermore, cytokines generated by neutrophils may establish a microenvironment that promotes angiogenesis, and thus promotes tumor growth and metastasis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism by which systemic inflammatory response markers influence cancer survival in these patients remain unclear, it is possible that pretreatment neutrophil and lymphocyte numbers reflect the level of inflammation within the tumor (24). Evidence is accumulating that cancer progression is influenced by the systemic inflammatory response (10,24,25). Furthermore, cytokines generated by neutrophils may establish a microenvironment that promotes angiogenesis, and thus promotes tumor growth and metastasis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to find novel indices with the prognostic utility to assist in predicting the clinical outcomes of HCC patients after TT. Existing research indicates that systemic inflammatory response and systemic nutritional status indicators are critical in the prognostic risk assessment of malignant tumors [ 13 ]. Besides, related studies have shown that inflammation directly affects tumor cell growth.…”
Section: Introductionmentioning
confidence: 99%